Validity E-Learning of Chemistry Learning Based on PjBL (Project Based Learning) Model for Thermochemistry Material with Flipped Classroom Approach for Eleventh Grade High School - Suci Sukmawati Syafei; Saniyyah Sausan; Hadistia Afifah; Efliani Efliani; Gunella Gunella (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2022)
Learning using e-learning with a blended learning model using the flipped classroom method is one of the learning systems suitable for use during the Covid-19 pandemic. This research has been carried out until the validity stage by producing an e-learning based on Project Based Learning (PjBL) on Thermochemistry material by applying the flipped classroom approach in the learning process. The type of research is R&D (Research and Development), with a 4-D model consisting of: (1) define, (2) design, (3) develop, and (4) disseminate. The products produced from the study were validated by 1 Chemistry lecturer of Faculty of Mathematics and Natural Sciences UNP and 1 chemistry teacher at MAN 2 Pesisir Selatan, and continued at the revision stage based on input from the validator. The analysis of the validity test was carried out using the Cohen kappa formula. Then obtained the kappa value of content validity of 0.884 and construct validity of 0.869 with very high categories for both. Based on this, based e-learning on Project Based Learning (PjBL) for Thermochemistry material is produced by applying a valid flipped classroom approach and can be used in the learning process.